A SEM-ANN analysis to examine the green consumption behavior of tourists in Vietnam - Huong, Nguyen Thi Quynh; Vinh, Nguyen Quang (International Journal of Innovative Research and Scientific Studies, 2025)
Environmental pollution has become a widespread issue across various sectors, necessitating effective solutions to enhance awareness and foster positive consumer attitudes towards eco-friendly products, particularly within the tourism industry. This study investigates the green consumption behavior of tourists in Vietnam using the Value-Attitude-Behavior (VAB) theoretical framework, focusing on key influencing factors and relationships. A hybrid SEM-ANN approach was applied, combining qualitative and quantitative methods. Data were collected from 526 tourists in Hanoi, Da Nang, and Ho Chi Minh City. Environmental consciousness and attitudes toward green advertising, environmental issues, and eco-social benefits significantly influence green consumption behavior. IPMA results show that environmental factors have the highest impact, followed by eco-social benefits, environmental issues, and green advertising. The analysis results also indicate the predictability of the ANN model compared with the SEM model, demonstrating the reasonableness of the SEM-ANN hybrid approach. The study also presents conclusions regarding its contributions to theoretical and practical aspects, as well as its limitations and directions for future research.